Comprehensive Analysis of a Dust Storm by a Lidar Network Combined With Multiple Data - Yang, Lili; Zhang, Shuwen; Tao, Huijie; Yang, Yanping; Wang, Lina; Cui, Yongfeng; Xu, Yanyan; Li, Xiaoyun (Frontiers in Environmental Science, 2022)
In order to improve the accuracy of dust storm prediction and reduce the damage and losses by dust storm event, it is necessary to conduct an in-depth study on dust storm event. The data of the national air quality stations, backward trajectories generated by Hybrid Single Particle Lagrangian Integrated Trajectory Model (HYSPLIT) and the lidar network data in Wuwei, Baiyin and Dingxi were used to study a large-scale dust storm event that occurred from 12 to 14 May, 2019. This paper explores the cause of the dust storm and physical characteristics of dust aerosols in three-dimensional space, as well as its impact on air quality. Results show that the dust storm was caused by the eastward movement of an East Asian Trough and affected most cities in northern China from northwest to Southeast. Consequently, the air quality was deteriorated seriously, especially over the Hexi Corridor. The hourly peak concentrations of PM10 in Wuwei and Baiyin were close to 3000 µg·m-3. The observations from the lidar network show that the dust intensities were similar at different cities and their extinction coefficients were close. However, the depolarization ratio varied with the sources and the physical characteristics of dust particles. According to the simulation results of extinction coefficients and particle concentrations, due to the impact of dust transported at high-altitude, the concentration of particles in Dingxi did not decrease with the increase of altitude. The particles concentrations from ground-based monitoring were lower than that of Baiyin and Wuwei, while its particles concentrations above 0.3 km were higher than that of Baiyin and Wuwei.